Factors associated with arterial stiffness assessed by pulse pressure amplification in healthy children and adolescents: a cross-sectional study - Leticia Pereira Salomão; Giselle Santos Magalhães; José Felippe Pinho da Silva; Luzia Maria dos Santos; Isabel Cristina Gomes Moura; Bruno Almeida Rezende; Maria Glória Rodrigues-Machado (BMC, 2023)
Abstract Background Increasing evidence suggests that reducing pulse pressure amplification (PPA) plays an important role in pathogenesis and progression of cardiovascular disease. This is a cross-sectional, observational, and analytical study in which we evaluated the associated factors with a greater chance of reducing PPA in 136 healthy children and adolescents aged 8 to 19 years old stratified by gender and age group. Methods Arterial stiffness and vascular and hemodynamic parameters were non-invasively measured using Mobil-O-Graph® (IEM, Stolberg, Germany), a cuff-based oscillometric device. PPA was expressed as the peripheral-to-central pulse pressure ratio (PPp / PPc). Participants with PPA < 1.49 were considered as part of the arterial stiffness group. Results In a univariate model, the increase in total vascular resistance, the reflection coefficient and the augmentation pressure were more likely to have arterial stiffness in all groups. The factors most likely to have arterial stiffness (as assessed by the reduction of the PPA) in the multivariate model were increasing age, the reflection coefficient and cardiac index in the total sample, male group and child and adolescent groups. In addition to age in the female group, cardiac output, stroke volume, and AIx@75 were the factors most likely to present arterial stiffness. Conclusions The results show for the first time in children and adolescents that the factors most likely to reduce PPA are related to the reflection wave, which determines aortic pressures and, therefore, left ventricular afterload.